Osteogenic differentiation and bone regeneration of iPSC-MSCs supported by a biomimetic nanofibrous scaffold. (1st January 2016) - Xie, Jing; Peng, Chen; Zhao, Qinghua; Wang, Xianliu; Yuan, Huihua; Yang, Liangliang; Li, Kai; Lou, Xiangxin; Zhang, Yanzhong
Graphical abstract: Abstract: Induced pluripotent stem cell-derived mesenchymal stem cells (iPSC-MSCs) are a new type of MSCs that come with attractive merits over the iPSCs per se. Aimed for regenerating bone tissues, this study was designed to investigate osteogenic differentiation and bone regeneration capacities of iPSC-MSCs by using biomimetic nanofibers of hydroxyapatite/collagen/chitosan (HAp/Col/CTS). Murine iPSCs were firstly induced to differentiate into iPSC-MSCs and thoroughly characterized. Effects of HAp/Col/CTS nanofibers prepared from electrospinning of Col-doped HAp/CTS nanocomposite, on osteogenic differentiation of the generated iPSC-MSCs were then evaluated in detail, including cell morphology, proliferation, migration, quantified specific osteogenic gene and protein expressions. Compared with different controls (TCP, CTS, and HAp/CTS), the HAp/Col/CTS scaffold was found to have more favorable effects on attachment and proliferation of iPSC-MSCs than others ( P < 0.01). Expressions of osteogenic genes, Runx2, Ocn, Alp, and Col, were significantly upregulated in iPSC-MSCs cultured on HAp/Col/CTS than CTS ( P < 0.01). Similarly, there appeared considerably higher secreting activities of osteogenesis protein markers, ALP and Col. Furthermore, mouse cranial defects were created to investigate efficacy of using iPSC-MSCs in combination with HAp/Col/CTS scaffold for regenerative bone repair in vivo . Examinations by computed tomography (CT) imaging, bone mineral density and hematoxylin eosin (HE) staining corroborated that cell-scaffold construct of iPSC-MSCs + HAp/Col/CTS could effectively promote bone regeneration. After 6 weeks of implantation, bone mineral density of the iPSC-MSCs + HAp/Col/CTS group was found to be nearly 2-fold higher than others. Our results demonstrated that biomimetic nanofibers of HAp/Col/CTS promoted the osteogenic differentiation and bone regeneration of iPSC-MSCs. The iPSC-MSCs + HAp/Col/CTS complex could be used as a new 'stem cell-scaffold' system for realizing personalized and efficacious bone regeneration in future. Statement of Significance: In bone tissue engineering, stem cells have become the most important source of seed cells. iPSC-MSCs are a new type of MSCs that come with attractive merits over the iPSCs per se. However, how to obtain befitting iPSC-MSCs and regulate their osteogenic differentiation are the key issues to be addressed. Given the great biomimicking capacity to extracellular matrix, electrospun nanofibers may be explored to modulate osteogenic differentiation of the iPSC-MSCs. This study successfully demonstrated that biomimetic nanofibers of HAp/Col/CTS significantly promoted the osteogenic differentiation and bone regeneration of iPSC-MSCs, which thereby suggests that nanofibrous scaffold supported iPSC-MSCs complex may be a new 'stem cell-scaffold' system for regulating the fate of osteogenic differentiation of iPSC-MSCs towards patient-specific bone regeneration in future.